Hope was here - Bauer, Joan, 1951- (Putnam, 2000)
When sixteen-year-old Hope and the aunt who has raised her move from Brooklyn to Mulhoney, Wisconsin, to work as waitress and cook in the Welcome Stairways diner, they become involved with the diner owner's political campaign to oust the town's corrupt mayor.